Tungsten-niobium co-doped nickel-rich ternary positive electrode material and preparation method thereof
Through the method of co-doping of tungsten and niobium dual elements, the nickel-rich ternary cathode material is modified, which solves the problems of limited stability and safety, and improves structural stability, cycle stability and thermal stability, which enhances the Battery rate performance and cycle stability.
Patent Information
- Application Number
- CN202411622755.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-14
AI Technical Summary
Nickel-rich ternary cathode materials have limited stability and safety problems in lithium-ion batteries, including cation mixing, surface structure instability, increased side reactions and microcrack formation.
Through the method of co-doping of tungsten and niobium dual element co-doping, the nickel-rich ternary cathode material is modified, and the synergistic action of tungsten and niobium is used to form a co-doped nickel-rich ternary cathode material, which significantly reduces the system energy of single-element doping. Reinforced material structural stability and cyclic stability.
The structural stability, cycle stability and thermal stability of nickel-rich ternary cathode materials have been significantly improved, which reduces the polarization of the electrode, improves the diffusion kinetics of lithium ions, and enhances the rate performance and cycle stability of the battery. .
Smart Images

Figure CN119461510A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of new energy materials, lithium-ion battery positive electrode materials, and specifically relates to a tungsten-niobium co-doped nickel-rich ternary positive electrode material and a preparation method thereof. Background Art
[0002] With the development of society, people are paying more and more attention to environmental pollution and energy crisis. The solution to these problems requires the continuous promotion of green, renewable energy and storage devices. The new generation of lithium-ion batteries has quickly taken a leading position in the fields of 3C digital and new energy vehicles due to its excellent performance, mature technology and green environmental protection. With the rapid development of new energy vehicles, people's demand for the range and service life of electric vehicles is constantly increasing. In order to solve the problems of long battery life and safety, the nickel-rich ternary cathode material LiNi x Co y Mn 1-x-y O2 (0.6≤x<1, 0<y≤0.20) has the advantages of higher specific capacity, low cost and environmental friendliness. As one of the most promising candidate materials for solving the above problems, it has become a research hotspot that researchers pay close attention to.
[0003] The nickel-cobalt-manganese ternary system has its own problems, just like other positive electrode materials on the market (lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, etc.). For example: the cobalt in lithium cobalt oxide is expensive and the cost is high; the structure of lithium manganese oxide is unstable during discharge and the battery safety performance is poor; lithium iron phosphate has low conductivity and poor high temperature performance. Although the nickel-cobalt-manganese ternary system battery can solve some problems to a certain extent through the combination of the three elements of nickel, cobalt and manganese, in the pursuit of high energy density of batteries, nickel-rich ternary positive electrode materials still have the defects of limited stability and safety.
[0004] Taking the nickel-rich ternary cathode material NCM811 as an example, it has become a popular material for lithium-ion battery cathodes due to its advantages such as high specific capacity. However, there are still many problems to be solved, which can be generally divided into problems inside the material crystal and on the surface of the material, including: (1) Li / Ni cation mixing, Li + with Ni 2+ The ionic radius is similar. During the charge and discharge process, the Ni in the transition metal layer 2+It will migrate to the lithium layer, occupy lithium vacancies, and form a cation mixed arrangement. (2) The surface structure of the material is unstable. During the cycle, the layered structure of the surface will transform into a spinel phase structure and an inert rock salt phase structure. (3) The transition metal on the surface of the material reacts with the electrolyte, causing the battery impedance to increase and the capacity to decay. (4) The secondary particles of the nickel-rich ternary positive electrode material are prone to microcracks. As the volume of the ternary material expands and contracts due to the insertion / deinsertion of lithium ions, cracks are formed near the grain boundaries inside the particles, and the crack surface will continue to react with the electrolyte. (5) The residual alkali on the surface will aggravate the side reactions between the active material and the electrolyte during the reaction process, and release gas, affecting the life and safety performance of the battery. Therefore, it is necessary to conduct in-depth research on the modification technology of nickel-rich ternary positive electrode materials. Further improving the physical and electrochemical properties of nickel-rich ternary positive electrode materials through modification has important scientific significance and practical application value.
[0005] In response to the above problems faced by nickel-rich ternary positive electrode materials, modification methods such as coating, doping, construction of concentration gradient positive electrode and synthesis of single crystal materials have been proposed to improve the physicochemical properties of nickel-rich ternary positive electrode materials. Among them, the two modification methods of coating and doping are more widely used. Coating modification is a simple and efficient modification method. Generally, a protective layer can be uniformly "covered" on the surface of nickel-rich positive electrode particles through wet chemical methods or atomic layer deposition, thereby isolating the direct contact between the electrolyte and the active electrode material, and protecting the particle surface and internal grain boundaries. In addition, some coating materials themselves have good electrical conductivity, which can reduce material impedance and enhance ion diffusion rate while stabilizing the material structure. Doping modification generally adds other metal cations or halogen anions to the crystal structure of the material to change the lattice constant or element valence state. Ion doping usually has an effect on Li + / Ni 2+ Mixing has an inhibitory effect, and the added ions often form more stable chemical bonds in the lattice, thereby stabilizing the crystal structure, reducing the structural collapse and phase change of the material, and improving the cycle stability. In addition, doping some materials with larger ion radius can also broaden the diffusion channel of lithium ions and improve the kinetic properties of the material.
[0006] However, most of the existing modification technologies for nickel-rich ternary cathode materials are single-element coating, doping, or single-element doping and coating integration. In the dual-element modification scheme for nickel-rich ternary cathode materials, one element is often used to dope the material, and the other element is used to coat the material. However, there is no case of simultaneous doping of high-priced dual elements in nickel-rich ternary cathode materials.
[0007] Therefore, by rationally designing a preparation method for realizing high-valent dual-element doping of nickel-rich ternary positive electrode materials, and the two high-valent elements have a synergistic effect, which has a greater modification effect than single-element doping, thereby guiding the synergistic doping of dual or multi-elements, it is one of the key exploration directions for the modification of nickel-rich ternary positive electrode materials at present and in the future. Summary of the invention
[0008] In view of this, the purpose of the present invention is to provide a nickel-rich ternary positive electrode material and a preparation method thereof in which tungsten and niobium dual elements play a synergistic role and co-doped modified.
[0009] In order to achieve the above objectives, the first objective of the present invention is to provide a method for preparing a tungsten-niobium co-doped nickel-rich ternary positive electrode material, using the following technical scheme:
[0010] A method for preparing a tungsten-niobium co-doped nickel-rich ternary positive electrode material comprises calcining a tungsten-niobium mixed pretreated precursor to obtain a dual-element co-doped nickel-rich ternary positive electrode material.
[0011] It is worth noting that the present invention realizes the dual-element doping of tungsten and niobium in the nickel-rich ternary positive electrode material simultaneously under the same calcination process conditions through a relatively simple process method, thereby effectively improving the rate performance and cycle stability of the nickel-rich ternary positive electrode material. In addition, the preparation method disclosed in the present invention requires a short preparation time, a simple operation process, and the selected raw materials are low in cost and easy to obtain, and the performance of the obtained materials is better than that of the unmodified nickel-rich ternary positive electrode material.
[0012] Furthermore, the specific steps of the preparation method include:
[0013] (1) mixing a nickel-rich ternary precursor with a tungsten source and a niobium source through an ethanol solution, heating, evaporating, and drying to obtain a nickel-rich ternary precursor pretreated with tungsten and niobium;
[0014] (2) The nickel-rich ternary precursor after tungsten-niobium pretreatment is mixed with a lithium source, ground, calcined, and cooled to obtain a tungsten-niobium co-doped nickel-rich ternary positive electrode material.
[0015] Compared with the dual-element modification scheme in the prior art in which one element is used to dope the material and the other element is used to coat the material, the present invention significantly reduces the system energy of single-element doping through dual-element co-doping. The dual-element synergistic effect makes doping easier to obtain, thereby realizing dual-element co-doping of nickel-rich ternary positive electrode materials.
[0016] Furthermore, in step (1), the nickel-rich ternary precursor is Ni x Co y Mn 1-x-y(OH)2, wherein 0.6≤x<1, 0<y≤0.20; the tungsten source is one or more of tungsten trioxide, lithium tungstate, sodium tungstate, and ammonium tungstate; the niobium source is one or more of niobium pentoxide, lithium niobate, and ammonium niobium oxalate.
[0017] It is worth noting that the nickel-cobalt-manganese ternary precursor used in the present invention can determine the specific ternary ratio for the nickel-rich ternary positive electrode material, and the tungsten source and niobium source used can stabilize the crystal structure of the positive electrode material, effectively inhibit the occurrence of side reactions, and improve the electrochemical properties of the positive electrode material.
[0018] Furthermore, the mass proportion of the tungsten source and the niobium source is 0.1%-5% of the mass of the nickel-rich ternary positive electrode material.
[0019] Furthermore, in step (2), the lithium source is one or a combination of lithium hydroxide and lithium carbonate.
[0020] Furthermore, the molar ratio of Li in the lithium source to Ni+Co+Mn in the nickel-rich ternary precursor is 1:(1.05-1.10).
[0021] It is worth noting that excess lithium can make up for the loss of lithium during the calcination process. A proper excess of lithium will increase the crystallinity of the material, reduce the mixing of lithium and nickel, and obtain a ternary positive electrode material with a better layered structure. However, too much lithium will increase the particle size, make the surface rough, reduce the insertion and extraction rate of lithium ions, reduce the conductivity of the positive electrode material, and thus reduce the rate capacity; and too much lithium will cause the residual alkali to react with the electrolyte to release gas, which will affect the safety and cycle life of the battery.
[0022] Furthermore, in the step (2), the calcination is divided into two steps, wherein the heating rate of the calcination is 2-6°C / min, and the calcination atmosphere is air and / or oxygen.
[0023] Furthermore, the first step calcination temperature range is 450-550°C, and the time is 4-8h; the second step calcination temperature range is 750-850°C, and the time is 13-18h.
[0024] Furthermore, in the step (2), the grinding time is 0.5-2h.
[0025] It is worth mentioning that suitable grinding conditions enable the secondary particles of the ternary positive electrode material to be effectively dispersed and mixed fully and evenly with the lithium source to obtain an ideal nickel-rich ternary positive electrode material.
[0026] The second object of the present invention is to provide a tungsten-niobium co-doped nickel-rich ternary positive electrode material prepared by the preparation method as described above.
[0027] A tungsten-niobium co-doped nickel-rich ternary cathode material, the chemical formula is: Li a Ni x Co y Mn 1-x-y (WNb) z O2, where 0.6≤x<1, 0<y≤0.20, 0.002≤z≤0.10; 1.0≤a≤1.10.
[0028] It is worth mentioning that the dual-element co-doped nickel-rich ternary positive electrode material obtained by the present invention changes the elemental composition of the nickel-rich ternary precursor. Only a small amount of dopant is used to effectively change the bonding strength and lattice parameters of the traditional nickel-rich ternary positive electrode material. In particular, a protective layer only a few nanometers thick is formed on the surface of the initial sample, thereby achieving a significant improvement in material properties, so that the dual-element co-doped nickel-rich ternary positive electrode material has excellent structural stability, cycle stability and thermal stability.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] 1. Compared with the traditional method of improving the cycle stability of the material by coating, doping, or doping-coating integration of a single element on the nickel-rich ternary cathode material, the present invention realizes the modification of the nickel-rich ternary cathode material by selecting tungsten and niobium elements with synergistic effects. Tungsten-niobium co-doping significantly reduces the system energy of single tungsten doping or single niobium doping, and double doping can further significantly improve the realization of the doping effect, effectively enhance the crystal structure of the nickel-rich ternary cathode material, and inhibit The anisotropic volume change caused by phase change maintains the integrity of the spherical secondary particles and prevents the formation of microcracks. The passivation layer formed by co-doping can prevent the occurrence of side reactions and the formation of microcracks, which is beneficial to inhibit the formation of internal oxygen vacancies and surface Li2CO3 and harmful gases, reduce the polarization of the electrode, and improve the diffusion kinetics of lithium ions, thereby improving the cycle stability and rate performance of the battery.
[0031] 2. The present invention can achieve the synergistic optimization modification of dual-element doping that is better than the undoped, single tungsten, and single niobium doping effects by simply calcining the tungsten-niobium mixed pretreated precursor. This is of great significance to the development of dual-element co-doped and multi-element co-doped modified nickel-rich ternary positive electrode materials.
[0032] 3. The preparation method of the tungsten-niobium co-doped nickel-rich ternary positive electrode material disclosed in the present invention is simple to operate. The required material can be obtained by calcining the pretreated precursor. The process is environmentally friendly, economical and suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without creative work.
[0034] Figure 1 The system energy diagrams of single tungsten doping, single niobium doping, and tungsten-niobium co-doping of the present invention, as well as the XRD diagrams of Example 1 and Comparative Examples 1-3.
[0035] Figure 2 It is the scanning electron microscope image of comparative example 1-3 of the present invention.
[0036] Figure 3 This is a scanning electron microscope image of Example 1 of the present invention.
[0037] Figure 4 HRTEM image of comparative example 1 of the present invention and Fourier transform image of the selected area.
[0038] Figure 5 HRTEM image of comparative example 2 of the present invention and Fourier transform image of the selected area.
[0039] Figure 6 HRTEM image of comparative example 3 of the present invention and Fourier transform image of the selected area.
[0040] Figure 7 HRTEM image of Example 1 of the present invention and Fourier transform image of the selected area.
[0041] Figure 8 The graphs are the cycle performances of Comparative Examples 1-3 and Example 1 of the present invention at different rates (1.0C, 5.0C, 10.0C).
[0042] Fig. 9 It is a rate performance diagram of comparative examples 1-3 and embodiment 1 of the present invention. DETAILED DESCRIPTION
[0043] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] The word "embodiment" used here as an "exemplary" does not necessarily mean that any embodiment described is superior to or better than other embodiments. Unless otherwise specified, the performance index tests in the embodiments of this application are performed using conventional test methods in the art. It should be understood that the terms described in this application are only used to describe specific implementation methods and are not used to limit the content disclosed in this application.
[0045] Unless otherwise specified, the technical and scientific terms used in this document have the same meanings as commonly understood by ordinary technicians in the technical field to which this application belongs; other experimental methods and technical means not specifically specified in this application refer to experimental methods and technical means commonly used by ordinary technicians in this field.
[0046] In order to better illustrate the content of the present application, numerous specific details are provided in the specific examples below. It should be understood by those skilled in the art that the present application can also be implemented without certain specific details. In the embodiments, some methods, means, instruments, equipment, etc. well known to those skilled in the art are not described in detail in order to highlight the main purpose of the present application.
[0047] Under the premise of no conflict, the technical features disclosed in the embodiments of the present application can be combined arbitrarily, and the resulting technical solutions belong to the contents disclosed in the embodiments of the present application.
[0048] The present invention discloses a method for preparing a tungsten-niobium co-doped nickel-rich ternary positive electrode material, which belongs to the technical field of new energy materials lithium-ion battery positive electrode materials. The present invention obtains a double-element co-doped nickel-rich ternary positive electrode material by calcining a tungsten-niobium mixed pre-treated precursor. The tungsten-niobium co-doping in the material significantly reduces the system energy of single tungsten doping or single niobium doping. And the co-doping makes the material have a more stable structure, inhibiting The anisotropic volume change caused by the phase transition maintains the integrity of the spherical secondary particles and prevents the formation of microcracks. In addition, the passivation layer formed by co-doping can prevent the occurrence of side reactions and the formation of microcracks. The synergistic effect of tungsten and niobium is also beneficial to inhibit the formation of internal oxygen vacancies and surface Li2CO3. Compared with undoped and single-element doped samples, the prepared co-doped samples can effectively enhance the structural stability of the material, reduce the polarization of the electrode, and improve the diffusion kinetics of lithium ions, thereby improving the cycle stability and rate performance of the battery at the same time.
[0049] In order to better understand the present invention, the present invention is further specifically described below through the following examples, but it should not be understood as a limitation of the present invention. Some non-essential improvements and adjustments made by technicians in this field based on the above invention content are also considered to fall within the protection scope of the present invention.
[0050] Example 1
[0051] The preparation method of tungsten-niobium co-doped nickel-rich ternary positive electrode material specifically comprises the following steps:
[0052] (1) 2.0 g of nickel-cobalt-manganese ternary precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2, 0.04g ammonium paratungstate and 0.04g ammonium niobium oxalate were uniformly added to the ethanol dispersant in sequence and stirred for 3h. Then, the above dispersion was stirred and heated in a water bath at 80℃ until the ethanol was completely evaporated, and then dried in a forced air drying oven at 80℃ for 6h to obtain a high nickel ternary cathode material precursor pretreated with tungsten and niobium dual elements.
[0053] Among them, the mass of ammonium paratungstate and ammonium niobium oxalate is 2% of the mass of the nickel-rich ternary positive electrode material precursor respectively.
[0054] (2) 1.8458g of the nickel-rich ternary cathode precursor material pretreated with tungsten and niobium was mixed and ground with 0.8895g of LiOH·H2O for 2h, then placed in a calcination furnace and calcined in two steps under an oxygen atmosphere. The temperature was raised to 500℃ at a rate of 5℃ / min and kept at that temperature for 6h, then continued to be raised to 800℃ and calcined for 15h. After cooling to 500℃ at a rate of 5℃ / min, the material was cooled in the furnace. Finally, a nickel-rich ternary cathode material co-modified with tungsten and niobium was obtained.
[0055] Among them, Li in lithium hydroxide and nickel-cobalt-manganese ternary precursor Ni 0.8 Co 0.1 Mn 0.1 The molar ratio of Ni+Co+Mn in (OH)2 is 1:1.06.
[0056] In order to further demonstrate the beneficial effects of the present invention and to better understand the present invention, the properties and application performance of the preparation method of the tungsten-niobium co-doped nickel-rich ternary positive electrode material disclosed in the present invention are further illustrated by the following comparative examples and performance tests, but they should not be understood as limitations of the present invention. The properties of the methods obtained by other measurement experiments conducted by technicians in this field based on the above-mentioned invention content and the applications based on the above-mentioned properties are also regarded as falling within the protection scope of the present invention.
[0057] Comparative Example 1
[0058] The preparation method of the original nickel-rich ternary positive electrode material specifically comprises the following steps:
[0059] 1.8458 g of the untreated nickel-cobalt-manganese ternary precursor Ni 0.8 Co 0.1 Mn 0.1(OH)2 was mixed with 0.8895g LiOH·H2O and ground for 2h, then placed in a calcination furnace and calcined in two steps under an oxygen atmosphere. The temperature was raised to 500℃ at a rate of 5℃ / min and kept at that temperature for 6h, then continued to be raised to 800℃ and calcined for 15h. After cooling to 500℃ at a rate of 5℃ / min, the mixture was cooled in the furnace. Finally, the original nickel-rich ternary positive electrode material was obtained.
[0060] Among them, Li in lithium hydroxide and nickel-cobalt-manganese ternary precursor Ni 0.8 Co 0.1 Mn 0.1 The molar ratio of Ni+Co+Mn in (OH)2 is 1:1.06.
[0061] Comparative Example 2
[0062] The preparation method of the nickel-rich ternary positive electrode material doped with tungsten single element specifically comprises the following steps:
[0063] (1) 2.0 g of nickel-cobalt-manganese ternary precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2 and 0.04g ammonium paratungstate were uniformly added to the ethanol dispersant in sequence and stirred for 3h. Then, the dispersion was stirred and heated in a water bath at 80℃ until the ethanol was completely evaporated, and then dried in a forced air drying oven at 80℃ for 6h to obtain a high nickel ternary cathode material precursor pretreated with tungsten element.
[0064] The mass of ammonium paratungstate is 2% of the mass of the nickel-rich ternary positive electrode material precursor.
[0065] (2) 1.8458g of tungsten-pretreated nickel-rich ternary cathode precursor material was mixed with 0.8895g of LiOH·H2O and ground for 2h, then placed in a calcination furnace and calcined in two steps under an oxygen atmosphere. The temperature was raised to 500℃ at a rate of 5℃ / min and kept at that temperature for 6h, then continued to rise to 800℃ and calcinated for 15h. After cooling to 500℃ at a rate of 5℃ / min, the material was cooled in the furnace. Finally, a single tungsten-modified nickel-rich ternary cathode material was obtained.
[0066] Among them, Li in lithium hydroxide and nickel-cobalt-manganese ternary precursor Ni 0.8 Co 0.1 Mn 0.1 The molar ratio of Ni+Co+Mn in (OH)2 is 1:1.06.
[0067] Comparative Example 3
[0068] The method for preparing a ternary nickel-rich positive electrode material doped with niobium single element specifically comprises the following steps:
[0069] (1) 2.0 g of nickel-cobalt-manganese ternary precursor Ni0.8 Co 0.1 Mn 0.1 (OH)2 and 0.04g of ammonium niobium oxalate were uniformly added to the ethanol dispersant in sequence and stirred for 3h. Then, the dispersion was stirred and heated in a water bath at 80℃ until the ethanol was completely evaporated, and then dried in a forced air drying oven at 80℃ for 6h to obtain a high nickel ternary cathode material precursor pretreated with niobium element.
[0070] Among them, the mass of ammonium niobium oxalate is 2% of the mass of the nickel-rich ternary positive electrode material precursor.
[0071] (2) 1.8458g of niobium-pretreated nickel-rich ternary cathode precursor material was mixed with 0.8895g of LiOH·H2O and ground for 2h, then placed in a calcination furnace and calcined in two steps under an oxygen atmosphere. The temperature was raised to 500℃ at a rate of 5℃ / min and kept at that temperature for 6h, then continued to be raised to 800℃ and calcined for 15h. After cooling to 500℃ at a rate of 5℃ / min, the material was cooled in the furnace. Finally, a single niobium-modified nickel-rich ternary cathode material was obtained.
[0072] Among them, Li in lithium hydroxide and nickel-cobalt-manganese ternary precursor Ni 0.8 Co 0.1 Mn 0.1 The molar ratio of Ni+Co+Mn in (OH)2 is 1:1.06.
[0073] Performance Testing
[0074] 1. X-ray diffraction (XRD) test
[0075] Figure 1 The system energy diagrams of single tungsten doping, single niobium doping, and tungsten-niobium co-doping, as well as the XRD diagrams of Example 1 and Comparative Examples 1-3.
[0076] Depend on Figure 1 It can be seen that, taking the crystal structure surface of Comparative Example 1 as the energy 0 point, theoretical calculations show that the addition of tungsten alone and niobium alone are both reflected in the fact that the added elements are easy to enter the body, resulting in a reduction in system energy, indicating that the addition of tungsten alone and niobium alone are both conducive to doping. In particular, the co-addition of tungsten and niobium further significantly reduces the system energy, indicating that the synergistic effect of tungsten and niobium is more conducive to doping, forming a co-doped nickel-rich ternary positive electrode material. The samples of Comparative Examples 1-3 and Example 1 are all typical α-NaFeO2 structures, belonging to Space group. The two main peaks of diffraction peaks (003) and (104) in Comparative Examples 1-3 and Example 1 are sharp, the (006) / (012) and (018) / (110) peaks are clearly split, and no obvious impurity phases are detected, indicating that the addition of tungsten and niobium does not change the crystal structure of the entire phase. However, the main peak (003) is offset, and the effects of the two elements of tungsten and niobium on the nickel-rich ternary positive electrode material are different. The (003) peak of the tungsten element modified sample shifts to a low angle, the (003) peak position of the niobium element modified sample does not change significantly, and the (003) peak position of the tungsten-niobium dual-doped sample moves between the tungsten modified sample and the niobium modified sample, showing the synergistic effect of the two elements. Overall, doping brings about changes in the lattice parameters and increases the interlayer spacing, which is beneficial to the diffusion of lithium ions during charging and discharging, thereby improving the electrochemical performance of the battery.
[0077] 2. Scanning electron microscope (SEM) test
[0078] Figure 2 They are the scanning electron microscope images of comparative examples 1-3, Figure 3 This is a scanning electron microscope image of Example 1.
[0079] All samples are composed of nanoscale primary particles aggregated to form spherical or quasi-spherical secondary particles, and the size of the secondary particles is about 5-10μm. The modification of tungsten and niobium elements did not significantly change the morphology of the secondary particles of the samples. However, it can be seen from the scanning electron microscope image that the primary particles of the single tungsten and single niobium modified samples are smaller than the primary particles of the unmodified samples, and the primary particles of the modified samples are more uniform and compact, making the secondary particles more tightly aggregated. This further shows that the addition of modified materials has a certain effect on the crystallization and growth of the materials during the calcination process. In particular, whether compared with the unmodified samples or compared with the single tungsten and single niobium modified samples, the primary particles of the tungsten-niobium dual-element doped synergistic modified samples are more uniform, and the secondary particles are smoother and more compactly aggregated, which is more conducive to preventing the structural collapse of the secondary particles during the charging and discharging process of the battery.
[0080] 3. High-resolution transmission electron microscopy (HRTEM) test and selected-area Fourier transform results
[0081] Figure 4 , Figure 5 , Figure 6 , Figure 7They are HRTEM images of Comparative Examples 1-3 and Example 1 and Fourier transform images of the selected area. It can be seen from the selected area Fourier transform analysis that there is a residual lithium layer on the surface of Comparative Example 1, and the interior is a standard layered phase; Due to the doping effect of tungsten element, the surface of the nickel-rich ternary positive electrode material in Comparative Example 2 is transformed into a spinel phase by doping, and the inside is a transition phase mixed with the spinel phase and the layered phase; Due to the doping effect of niobium element, the surface of the nickel-rich ternary positive electrode material in Comparative Example 3 is transformed into a rock salt phase by doping, and the inside is also a transition phase mixed with the rock salt phase and the layered phase; and Example 1 is co-doped due to the synergistic effect of tungsten and niobium, and a thicker rock salt phase layer is formed on the surface of the nickel-rich positive electrode material than the single element modification, and the inside is a transition phase mixed with the rock salt phase and the layered phase, and the inside of the particle is still a layered phase. The foreign phases formed by modification (such as spinel phase and rock salt phase) are different from the foreign phases that appear during the battery cycle. The foreign phase originates from the partial mixing of Li and Ni ions, where the spinel phase represents an intermediate state between the layered phase and the rock salt phase. For the layered phase, Li occupies only the 3a position and TM occupies the 3b position, while for the rock salt phase, Li and TM occupy randomly in 3a and 3b. Unlike the direct transformation of LiNiO2 (LNO) from the layered phase to the rock salt phase during the doping process, the presence of Co and Mn will prevent the transformation of NCM from the layered phase to the rock salt phase brought about by the complete mixing of Li and TM, resulting in the possibility that NCM may undergo an intermediate transformation to the spinel phase. The foreign phase formed by surface modification rather than structural degradation is beneficial to the cyclic stability of the material. W doping forms the spinel phase due to the inhibition of Li and TM mixing by Co and Mn. Nb doping destroys the inhibitory effect of Co and Mn on the mixing of Li and TM, resulting in the direct formation of the rock salt phase. However, increasing the mixing of Li and Ni by niobium modification is unfavorable. The synergistic effect of tungsten and niobium not only forms a protective layer of the rock salt phase but also reduces the severe mixing of Li and Ni. The doped sample forms a layer before the battery is charged and discharged, which is beneficial to the stability of the material in the subsequent cycle process, thereby enhancing the material's cycle stability. Compared with tungsten and niobium single element doped samples, tungsten and niobium co-doped samples have a more stable protective layer, so they can more significantly enhance the material's cycle stability.
[0082] 4. Cycle and rate performance test
[0083] Comparative Examples 1-3 and Example 1 were used as positive electrodes and assembled into button cells with metal lithium sheets as negative electrodes, and their cycle and rate performance were tested in the voltage range of 2.8-4.4V. The results are shown in Tables 1 and Figure 8-9 As shown. Among them, Figure 8 The cycle performance diagrams of Comparative Examples 1-3 and Example 1 at different rates (1.0C, 5.0C, 10.0C) are shown in FIG. Fig. 9 It is a rate performance diagram of ratios 1-3 and Example 1.
[0084] Table 1 Button battery performance test results
[0085]
[0086] From Table 1 and Figure 8 It can be seen that in the voltage range of 2.8-4.4V, except for the loss of initial capacity at a low current of 0.2C, the capacity retention rates of the tungsten and niobium single-element doped and tungsten-niobium co-doped nickel-rich ternary positive electrode materials prepared in Comparative Examples 2-3 and Example 1 after 300 cycles at 1.0C and 5.0C current densities and 350 cycles at 10.0C current density are higher than those of Comparative Example 1. The loss of initial capacity is due to the fact that the nanoscale protective layer formed by doping does not contribute to the capacity, but the capacity loss is limited. The above results show that the tungsten-niobium dual-element co-doped sample of Example 1 is the best embodiment, and the capacity retention rate after 350 cycles at a high current of 10.0C is increased by 38.1% relative to that of Comparative Example 1.
[0087] The above experiments show that the cycle stability of the tungsten-niobium co-doped nickel-rich ternary positive electrode material prepared by the present invention is significantly improved.
[0088] Depend on Fig. 9 It can be seen that the high rate discharge capacity of Comparative Examples 2-3 and Example 1 is more advantageous. Among them, the 10.0C high rate capacity of Example 1 is as high as 142.0 mAh / g, which is 27.0 mAh / g higher than that of Comparative Example 1 at 10.0C high rate.
[0089] Both the cycle stability and rate performance indicate that the method of the present invention is significantly effective and improves the electrochemical performance of the positive electrode material.
[0090] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a tungsten-niobium co-doped nickel-rich ternary positive electrode material, characterized in that: The double-element co-doped nickel-rich ternary positive electrode material is obtained by calcining a tungsten-niobium mixed pretreated precursor.
2. The preparation method according to claim 1, characterized in that: The specific steps include: (1) mixing a nickel-rich ternary precursor with a tungsten source and a niobium source through an ethanol solution, heating, evaporating, and drying to obtain a nickel-rich ternary precursor pretreated with tungsten and niobium; (2) The nickel-rich ternary precursor after tungsten-niobium pretreatment is mixed with a lithium source, ground, calcined, and cooled to obtain a tungsten-niobium co-doped nickel-rich ternary positive electrode material.
3. The preparation method according to claim 2, characterized in that: In the step (1), the nickel-rich ternary precursor is Ni x Co y Mn 1-x-y (OH)2, wherein 0.6≤x<1, 0<y≤0.20; the tungsten source is one or more of tungsten trioxide, lithium tungstate, sodium tungstate, and ammonium tungstate; the niobium source is one or more of niobium pentoxide, lithium niobate, and ammonium niobium oxalate.
4. The preparation method according to claim 3, characterized in that: The mass proportion of the tungsten source and the niobium source is 0.1%-5% of the mass of the nickel-rich ternary positive electrode material.
5. The preparation method according to claim 2, characterized in that: In the step (2), the lithium source is one or a combination of lithium hydroxide and lithium carbonate.
6. The preparation method according to claim 5, characterized in that: The molar ratio of Li in the lithium source to Ni+Co+Mn in the nickel-rich ternary precursor is 1:(1.05-1.10).
7. The preparation method according to claim 2, characterized in that: In the step (2), the calcination is divided into two steps, wherein the heating rate of the calcination is 2-6°C / min, and the calcination atmosphere is air and / or oxygen.
8. The preparation method according to claim 7, characterized in that: The first step calcination temperature range is 450-550° C., and the time is 4-8 hours; the second step calcination temperature range is 750-850° C., and the time is 13-18 hours.
9. The preparation method according to claim 2, characterized in that: In the step (2), the grinding time is 0.5-2h.
10. A tungsten-niobium co-doped nickel-rich ternary positive electrode material prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The chemical formula of the tungsten-niobium co-doped nickel-rich ternary positive electrode material is: Li a Ni x Co y Mn 1-x-y (WNb) z O2, where 0.6≤x<1, 0<y≤0.20, 0.002≤z≤0.10; 1.0≤a≤1.10.
Citation Information
Patent Citations
A tungsten ion doped high-nickel layered oxide lithium electrode material and a preparation method thereof
CN109167056A
Multi-element mixed doping coating modified ternary positive electrode material and preparation method thereof
CN109192972A
Multi-element in-situ co-doped ternary material precursor as well as preparation method and application thereof
CN109336193A
High-nickel low-cobalt type high-voltage-resistant ternary positive electrode material and preparation method thereof
CN111384392A
Composite metal oxide doped positive electrode material, preparation method thereof and lithium ion battery
CN113445127A
Cited By
Preparation method and application of high-temperature-resistant lithium iron phosphate positive electrode material based on solid solution reaction
CN120757091A
Preparation method and application of high-temperature-resistant lithium iron phosphate positive electrode material based on solid solution reaction
CN120757091B